2015
DOI: 10.1090/tran/6442
|View full text |Cite
|
Sign up to set email alerts
|

Finite-dimensional invariant subspace property and amenability for a class of Banach algebras

Abstract: Motivated by a result of Ky Fan in 1965, we establish a characterization of a left amenable F-algebra (which includes the group algebra and the Fourier algebra of a locally compact group and quantum group algebras, or more generally the predual algebra of a Hopf von Neumann algebra) in terms of a finite dimensional invariant subspace property. This is done by first revealing a fixed point property for the semigroup of norm one positive linear functionals in the algebra. Our result answers an open question post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…However, 1 (Z) does not have the fpp for bounded closed convex sets [9]. In a recent remarkable paper of Lin [25], it was shown that 1 (Z) can be renormed to have the fpp. This answers in negative a long-standing open question of whether every Banach space with the fpp is necessarily reflexive.…”
Section: Introductionmentioning
confidence: 99%
“…However, 1 (Z) does not have the fpp for bounded closed convex sets [9]. In a recent remarkable paper of Lin [25], it was shown that 1 (Z) can be renormed to have the fpp. This answers in negative a long-standing open question of whether every Banach space with the fpp is necessarily reflexive.…”
Section: Introductionmentioning
confidence: 99%
“…S ×E → E is continuous, then S is jointly continuous on compact sets. The following result was proved in [57].…”
Section: Fixed Point Properties For F-algebrasmentioning
confidence: 87%
“…As we have known, P 1 (A) is indeed a metric topological semigroup with the product and topology inherited from A. The following was proved in [57]. A semitopological semigroup S is extremely left amenable if LUC(S) has a multiplicative left invariant mean.…”
Section: Fixed Point Properties For F-algebrasmentioning
confidence: 95%
See 1 more Smart Citation
“…Finite-dimensional invariant subspace property of Ky Fan and the Hahn-Banach extension property for amenable Banach algebras. Motivated by a result of Ky Fan in 1965, the authors of [33] establish a characterization of a left-amenable F -algebra (which includes the group algebra and the Fourier algebra of a locally compact group, the predual L 1 (G) of a locally compact quantum group G, or, more generally, the predual algebra of a Hopf-von Neumann algebra) in terms of a finite-dimensional invariant subspace property. This is done by first exhibiting a fixed-point property for the semigroup of norm-one positive linear functionals on the algebra.…”
Section: 7mentioning
confidence: 99%